BARC–IRRI Consultation Meeting for the Prioritization of Innovations: Workshop proceedings - International Rice Research Institute (International Rice Research Institute, 2025)
The Consultation and Prioritization Workshop for the CGIAR Scaling for Impact (S4I) Program in Bangladesh was held on 18 August 2025 at the Bangladesh Agricultural Research Council (BARC), Dhaka. Convened jointly by BARC and the International Rice Research Institute (IRRI), the workshop aimed to support country-led prioritization of mature and high-potential CGIAR innovations for accelerated scaling. The consultation facilitated alignment between CGIAR and IRRI innovation portfolios and national research and development priorities, strengthened coordination with the National Agricultural Research and Extension System (NARES), and identified system-level constraints and opportunities for scaling in climate-vulnerable agro-ecosystems. Key thematic areas included coastal polder water management, synchronized cropping systems, crop diversification, social and gender-responsive innovations, and digital advisory and decision-support tools. Through structured discussions, participants prioritized water management and drainage-focused innovations, collective action-based cropping systems, Alternate Wetting and Drying (AWD), and scalable digital platforms as near-term opportunities for impact. The workshop concluded with agreement on follow-up actions, including thematic workshops, policy dialogues, and joint planning processes to operationalize scaling pathways under the CGIAR S4I Program in Bangladesh.